Editor's Letter 12.2. Issue 2 (27th July 2020) - Unknown
Abstract : The editor‐in‐chief, Dr. Connie Snyder Mick, introduces the articles in this issue, noting their publication during the challenges of the COVID‐19 global pandemic and the social unrest in the United States focused on racial justice. 摘要: 主编Connie Snyder Mick博士介绍本期收录的文章, 特别指出文章发表于COVID‐19全球大流行和美国关于种族正义的社会动荡挑战期间。 Resumen: La editora principal, la Dra. Connie Snyder Mick, presenta los artículos en este número y señala su publicación durante los desafíos de la pandemia global COVID‐19 y los disturbios sociales en los Estados Unidos centrados en la justicia racial.